Heterogeneous Labor, Labor Market Frictions and Employment Effects of Technological Change. Theory and Empirical Evidence for the U.S. and Europe - Jens Rubart (Technische Universität Darmstadt, Department of Law and Economics, 2006)
During the last two decades the so called IT revolution has led to a diverse pattern of growth and employment in OECD countries. In particular, anglo-saxon economies like the U.S. or the U.K. exhibited high rates of economic performance and low unemployment rates, whereas continental European countries showed low economic growth and high unemployment rates. Based on the findings of Lindquist (2004) that the relative demand for workers of different skills (measured by the variation of educational wage differences) varies significantly over the business cycle, we develop a dynamic general equilibrium model which accounts for skill biased technology shocks as well as for the employment record of labor which is divided into different categories of skills. Furthermore, the labor market is characterized by search and matching frictions which allows us to analyze different kinds of institutional settings which determine the negotiated wage rates as well as the demand for labor of the respective skill group. In particular, the latter assumption enables us to control for stylized facts of continental European labor markets. By confronting our theoretical results to empirical evidences it is shown that labor market frictions are necessary to reproduce empirical findings as the lagged response of output, wages and employment after unanticipated shocks to technology.
Keywords: E32; J21; J23; J24; J31; J41; 330; DGE Model; Heterogenous Labor; Skill Biased Technological Change; Search Unemployment